2019
DOI: 10.1039/c9dt01932d
|View full text |Cite
|
Sign up to set email alerts
|

Polymorph nickel titanate nanofibers as bifunctional electrocatalysts towards hydrogen and oxygen evolution reactions

Abstract: Rationality between the morphology and composition of spinel and ilmenite polymorphs helps in the design of electrodes from nickel titanate nanofibers for bifunctional electrocatalytic water-splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Water splitting has been attracting increasing attention owing to its possibility of substituting conventional fossil fuels and generating clean energy. [ 1–4 ] The overall reaction for water splitting is categorized into two half‐cell reactions: hydrogen evolution reaction (HER) [ 5–7 ] at the cathode and the oxygen evolution reaction (OER) [ 8–10 ] at the anode. Several studies have reported the improvement in the catalytic performance of each reaction; still a simplified system as well as improvement in the overall water splitting performance of a full cell have been continuously proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water splitting has been attracting increasing attention owing to its possibility of substituting conventional fossil fuels and generating clean energy. [ 1–4 ] The overall reaction for water splitting is categorized into two half‐cell reactions: hydrogen evolution reaction (HER) [ 5–7 ] at the cathode and the oxygen evolution reaction (OER) [ 8–10 ] at the anode. Several studies have reported the improvement in the catalytic performance of each reaction; still a simplified system as well as improvement in the overall water splitting performance of a full cell have been continuously proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Water splitting has been attracting increasing attention owing to its possibility of substituting conventional fossil fuels and generating clean energy. [1][2][3][4] The overall reaction for water splitting is categorized into two half-cell reactions: hydrogen evolution reaction (HER) [5][6][7] at the cathode and the oxygen evolution as a truly bifunctional catalyst is a daunting task. However, achieving the above goal solely by experiments is not feasible because of the enormous size of the design space, given the various components and compositions.…”
Section: Introductionmentioning
confidence: 99%
“…6 Generally, electrocatalytic water splitting occurs in two core half-reactions: the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER), both of which have sluggish reaction kinetics and are highly dependent on high-performance but precious electrocatalysts with lower overpotentials and accomplish favorable energy-transfer efficiency for activation. 5,7 Currently, precious RuO 2 /IrO 2 and Pt are the benchmark electrocatalysts for the OER and HER, respectively. 8,9 However, their scarcity and high cost have hampered their large-scale application.…”
Section: Introductionmentioning
confidence: 99%